Natural edges & hollow forms [ a lesson with Chris Stott - Stott, Chris; Gordon Video Services (South Humberside : Chris Stott Videos, 1994)
"The tape is intended to guide and help the more adventurous turner who wants to develop his work into the field of natural edges and to test his skills by making hollow forms"
filmed and produced by Gordon Video Services for Chris Stott
Keywords: Turning (Lathe work); Woodwork